Gingival overgrowth by calcium channel blockers - Ocaña Diestra, Tania (2014)
Aim: To determine the frequency of gingival overgrowth in hypertensive patients taking calcium channelblockers drugs and compare it to another group of patients who do not take these hypertensive drugs, was the aim of this study. Methodology: In the cross-sectional descriptive study, we evaluated 50 hypertensive patients who were taking calcium channel blockers (study group) and 50 hypertensive patients receiving treatment with other type of antihypertensive (control group). We used a data collectedinstrument, periodontogram and photographs of gingival overgrowth. Results: it was found that 10% of patients taking calcium channel blockers showed gingival overgrowth, in control group were not found any patients with this condition and the difference was statistical significance (p < 0.05). There was an inverse trend with respect to age, because while age increased, the frequency of gingivalovergrowth decreased, but it was not statistically significant. Conclusions: 10% of patients using antihypertensive calcium channel blockers had gingival overgrowth, which was statistically significant compared to control group. Gender, age and arcade affected are not related to gingival overgrowth in the sample studied.